Critical review of analytical methods for the determination of flame retardants in human matrices - Hajeb, Parvaneh; Castaño, Argelia; Cequier, Enrique; Covaci, Adrian; López, Marta Esteban; Antuña, Ana Gonzalez; Haug, Line Småstuen; Henríquez-Hernández, Luis Alberto; Melymuk, Lisa; Pérez Luzardo, Octavio; Thomsen, Cathrine; Vorkamp, Katrin (Analytica chimica acta, 2022)
Human biomonitoring is a powerful approach in assessing exposure to environmental pollutants. Flame retardants (FRs) are of particular concern due to their wide distribution in the environment and adverse health effects. This article reviews studies published in 2009-2020 on the chemical analysis of FRs in a variety of human samples and discusses the characteristics of the analytical methods applied to different FR biomarkers of exposure, including polybrominated diphenyl ethers (PBDEs), hexabromocyclododecane (HBCD), novel halogenated flame retardants (NHFRs), bromophenols, incl. tetrabromobisphenol A (TBBPA), and organophosphorous flame retardants (PFRs). Among the extraction techniques, liquid-liquid extraction (LLE) and solid phase extraction (SPE) were used most frequently due to the good efficiencies in the isolation of the majority of the FR biomarkers, but with challenges for highly lipophilic FRs. Gas chromatography-mass spectrometry (GC-MS) is mainly applied in the instrumental analysis of PBDEs and most NHFRs, with recent inclusions of GC-MS/MS and high resolution MS techniques. Liquid chromatography-MS/MS is mainly applied to HBCD, bromophenols, incl. TBBPA, and PFRs (including metabolites), however, GC-based analysis following derivatization has also been used for phenolic compounds and PFR metabolites. Developments are noticed towards more universal analytical methods, which enable widening method scopes in the human biomonitoring of FRs. Challenges exist with regard to sensitivity required for the low concentrations of FRs in the general population and limited sample material for some human matrices. A strong focus on quality assurance/quality control (QA/QC) measures is required in the analysis of FR biomarkers in human samples, related to their variety of physical-chemical properties, low levels in most human samples and the risk of contamination.
Keywords: halogenované difenylethery; extrakce na pevné fázi; HBM4EU; Novel halogenated flame retardants; tandemová hmotnostní spektrometrie; Organophosphorous flame retardants; Humans; Emerging contaminants; Human biomonitoring; Tandem Mass Spectrometry; Halogenated Diphenyl Ethers; Gas Chromatography-Mass Spectrometry; retardanty hoření; plynová chromatografie s hmotnostně spektrometrickou detekcí; lidé; Solid Phase Extraction; Flame Retardants